The Political Economy of Indonesia's Downstream Industrialization: Resource Governance and Global Supply Chains - Intan Larasati Putri (Indonesian Political Transformation, 2026)
Indonesia's downstream industrialization strategy has emerged as a central pillar of national economic transformation by promoting domestic processing of strategic natural resources and reducing dependence on raw commodity exports. While the policy has attracted substantial foreign investment and strengthened Indonesia's role in global manufacturing networks, it has also generated important debates concerning governance, industrial competitiveness, environmental sustainability, and international trade relations. This study examines the political economy of Indonesia's downstream industrialization through the lens of resource governance and global supply chain restructuring. Employing a qualitative political economy approach, the research analyzes industrial policy documents, investment trends, trade statistics, regulatory reforms, and interviews with policymakers, industry representatives, labor organizations, and international investors. The findings indicate that downstream industrialization has significantly enhanced Indonesia's bargaining position within global value chains, particularly in strategic sectors supporting renewable energy technologies. However, institutional fragmentation, environmental governance challenges, labor issues, and evolving international trade regulations continue to influence long-term policy effectiveness. The article argues that successful industrial transformation depends upon coherent governance institutions capable of balancing economic nationalism with global market integration and sustainable development objectives. By integrating theories of developmental states, industrial policy, and global political economy, the study contributes to broader debates concerning industrial upgrading in emerging economies. The findings provide policy lessons for resource-rich developing countries seeking to strengthen domestic industrial capacity while maintaining international competitiveness and environmental responsibility.